Implementation of No Smoking Area Policy in Palu City - M Syukur; Syahruddin Hattab; Nasir Mangngasing (UIN Sunan Gunung Djati, 2024)
This study aims to determine the Implementation of the No Smoking Area Policy in Palu City. The type of research used is descriptive qualitative. The type of data used primary data and secondary data. Data collection techniques, conducted through observation, interviews, and documentation. The technique of withdrawing informants using purposive. The data analysis used is the Miles, Huberman and Saldana model, namely data collection, data presentation, data condensation and conclusion drawing. More efforts are needed to optimize the implementation of the smoke-free area policy in Palu City, including conducting a lot of education-based socialization about the dangers of cigarette smoke for both active and passive smokers, as well as instilling more understanding to every agency related to the implementation of smoke-free areas, because being free from cigarette smoke and breathing clean air is a community right guaranteed by the government. The smoke-free area (KTR) policy in Palu City has not been fully responded to by all policy stakeholders in Palu City. As a result, the implementation of the smoke-free area policy has not been effective. Based on the results of the research conducted, it can be concluded that the implementation of the smoke-free area policy in Palu City is relatively ineffective, due to several things, namely cross-sectoral communication has never been carried out by policy implementers. The consistency of the implementers of the smoke-free area (KTR) policy is still low. Socialization to the community is very minimal. Lack of community compliance, as well as non-enforcement of sanctions and fines for people who deliberately violate the smoke-free area policy.